(untitled) (Nigerian Journal of Physiological Sciences, 2024)
When Severe Acute Respiratory human Coronavirus 2 (SARS-hCOV 2) infection began in December 2019, detailed knowledge about the virus was lacking. This included non-availability of anti-viral treatment or vaccine, no knowledge of virus-human interaction, and lack of prognostic factors for stages of illness among others. A publication in Nigerian Journal of Physiological Sciences (2020). 35: 20-25 titled “Immune Responses During Human Coronavirus Infection: Suggestions For Future Studies” adduced investigations into immune parameters of COVID-19 patients so as to throw more light on the immunopathogenesis of SAR-CoV-2 infection, in order to create avenue for the development of vaccines or herd immunity. This present publication is a review of studies carried out on COVID-19 patients in one Infectious Diseases Center (I.D.C), Ibadan, Nigeria as a response to the gaps in knowledge raised in above mentioned publication. Cummulatively, immune-metabolic studies from this IDC revealed mild, age- and sex-dependent status of COVID-19 in patients admitted into this center. Thus, explaining the basis for the effectiveness of adopted re-purposed drugs (chloroquine or hydroxychloroquine, zinc, vitamins C and D and or antibiotics), physiotherapy and nutritional support used for the management of admitted COVID-19 patients. Also, this paper vindicated that inflammation was heightened during SARS-CoV 2 infection; therefore therapeutic interventions to control the inflammatory processes, oxidative stress, antibodies against structural and non-structural proteins or blocks receptor sites were proposed. In addition, development of herd immunity and efficacy of COVID-19 vaccines (Astrazeneca and Moderna) were elucidated in general population. However, study to determine host genetic factors in hCoV infection was lacking. This review concluded that interdisciplinary collaborative approach will be useful in the management of future emerging or re-emerging infection